View On Malaysian Law Of Youth Development - Asmah Laili Hj Yeon; Zainal Amin Ayub; Alias Azhar; Siti Alida John Abdullah; Rozita Arshad (UUM Journal of Legal Studies, 2016)
49% of the total numbers of citizens of Malaysia are under the category of youth which is equivalent to 13.74 million people.  Therefore, their contribution to the nation in education, economy, politics, social and governance are very significant.  There is dilemma in defining legal age of youth not only in Malaysia but in global scenario, the issue of their awareness in youth development law and youth legal rights which are not documented in the statute. In light of the above gap, this paper examines and analyses legal challenges of current and future challenges of youth development law in Malaysia. This study adopts two approaches i.e. quantitative and qualitative approaches.  For quantitative approach, an exploratory (socio-legal) survey technique using questionnaire has been conducted among youth in Malaysia to investigate their awareness in relations to law of youth development.  The descriptive analysis is to describe level of youth awareness in relation to youth development law and the analytical analysis is to investigate deeply, and evaluate every aspect of legal provisions with regard to youth law. It is suggested that the Malaysian government should amend the definition of youth according to the international standard, initiate more programmes to increase the awareness of youth regarding the law and give a consideration to insert provision of youth rights in the Act.